Green Growth in Algeria: Balancing Industry and Environment for Sustainable Economic Development - Bouazza Elamine ZEMRI (Dirassat Journal Economic Issue, 2024)
This study investigates the sustainable economic development of Algeria's industry from 1990 to 2021, focusing on the transition towards green growth. Employing a database for three industrial branches (hydrocarbon; iron, steel and mining; building materials) and a semi-logarithmic production function, the study evaluates the productivity changes in industrial workers and the implications for green growth using the KELM model. The findings reveal a decrease in CO2 emissions and a significant rise in energy efficiency and productivity. These changes reflect the industry's movement towards sustainable economic growth, emphasizing renewable energy and low-carbon industries. The study concludes that while Algeria has made progress towards balancing industrial growth and environmental sustainability, further development in new green sectors is crucial for achieving a more sustainable economic model.